Recent Advancements in Spectrophotometric pKa Determinations: A Review - Berkhout, Job Herman; HN, Aswatha Ram (Indian Journal of Pharmaceutical Education and Research, 2019)
The pKa value is a key feature in Absorption, Distribution, Metabolism and Excretion (ADME) of drugs, thus knowing this value is critical in drug development. In this review, pKa values determined in the past decade, using UV-Vis spectrometry, are discussed. To determine the pKa, four methods were applied; Henderson-Hasselbach, Albert-Serjeant, Bates-Schwarzenbach and Spectrometric titrations. This review will show the value of this aged but well-established technique in the past decade, due to its simplicity, accuracy, cost efficiency and reproducibility.
Keywords: Albert-Serjeant; Bates-Schwarzenbach; Henderson-Hasselbach; pKa; Spectroscopy; Titrations